Fumed alumina powder with reduced moisture content
Patent Information
- Application Number
- JP2023567054
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-05-14
- Filing Date
- 2022-05-03
- Publication Date
- 2025-04-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing methods fail to produce fumed alumina powder with low water content and high alpha-aluminum oxide content, which is suitable for applications like lithium ion batteries, while maintaining good dispersibility and avoiding structural changes.
A method involving heat treatment of fumed alumina at specific temperatures and conditions, combined with minimal water exposure, to achieve a fumed alumina powder with less than 5% alpha-Al2O3, low water content, and controlled particle size distribution.
The method produces fumed alumina with reduced water content, maintaining high BET surface area and dispersibility, suitable for lithium ion batteries without significant structural changes.
Smart Images

Figure 00000021_0000 
Figure 00000021_0001 
Figure 00000021_0002
Abstract
Description
[Technical field]
[0001] The present invention relates to a fumed alumina powder having a relatively small particle size and low moisture content, its method of preparation and uses. [Background technology]
[0002] Fumed alumina powder is a very useful additive for a variety of applications. To name just a few of these applications, fumed alumina can be used as a rheology modifier or anti-settling agent in paints, coatings, silicones, and other liquid systems. Alumina powder can improve powder flow or optimize the mechanical or optical properties of silicone compositions, as well as be used as a filler in pharmaceuticals or cosmetics, adhesives or sealants, toners, and other compositions. Fumed alumina can be used as a catalyst support, in chemical mechanical planarization (CMP) applications, in insulation, and in lithium-ion batteries.
[0003] Fumed alumina may contain various crystalline phases such as alpha-, theta-, delta-, and gamma-Al2O3. The presence and ratio of these crystalline phases largely determine the physicochemical properties of fumed alumina and its applicability in various fields.
[0004] Untreated fumed aluminum oxide is hydrophilic due to the presence of polar hydroxyl groups on its surface. Such untreated fumed alumina tends to absorb a significant amount of water, increasing the moisture content of such materials. Part of the absorbed water is weakly bound to Al2O3 and can be removed after drying for example at about 100 °C for 1-2 h. The content of such weakly bound water may depend on the humidity of the environment in which the alumina is stored after preparation. Another part of the absorbed water is more strongly bound to Al2O3 and cannot be removed even by drying at 150 °C for 2 h. This strongly bound water content is almost independent of storage conditions. The total moisture content of aluminum oxide, including both types of absorbed water, can be reliably measured by Karl Fischer titration.
[0005] In some applications, such as lithium ion battery components such as separators, electrodes, and electrolytes, the presence of water is undesirable.
[0006] Thus, WO 2018 / 149834 discloses the preparation of mixed lithium metal oxide particles coated with fumed aluminum oxide and titanium dioxide, and the use of this material in lithium-ion batteries.
[0007] WO 2020 / 225018 discloses a separator for a lithium-ion battery comprising an organic substrate coated with a coating layer comprising a binder and surface-treated fumed alumina.
[0008] The water present in such alumina additives can react with some of the water-sensitive components of lithium-ion batteries, such as LiPF6, which is often included in the electrolyte and can cause the electrolyte to decompose, releasing reactive materials such as HF, which can promote the passivation of such batteries. Therefore, fumed alumina with reduced water content may be necessary or useful for applications involving water-sensitive components.
[0009] In many cases, water that is weakly bound to fumed alumina can be removed by drying under mild conditions, but water that is tightly bound to Al2O3 usually cannot be removed without significant changes to the structure and physicochemical properties of the fumed alumina used. Therefore, the problem of how to obtain such fumed alumina powders with low moisture content remains unsolved.
[0010] Description of the Prior Art A typical process for producing fumed alumina powder is described in WO 2005 / 061385. It involves flame hydrolysis of aluminium chloride vapour followed by separation of solid aluminium oxide from the gas stream and subsequent treatment of the solid product with steam to purify the alumina from the hydrogen chloride residues. The alumina powder samples prepared have a tamped density of 24-31 g / L and a BET surface area of 101-195 m. 2 / g, is predominantly amorphous or in the gamma phase, and has a hydroxyl content of 8.1-11.4 OH / nm as determined by reaction with lithium aluminum hydride. 2 The presence of water during the flame hydrolysis process and the subsequent post-treatment of the fumed alumina with steam or moist air produces fumed aluminium oxide with a relatively high water content (loss on drying at 105°C for 2 hours up to 5% by weight).
[0011] Similarly, WO 2006 / 067127 reports that BET surface areas between 49 and 175 m 2 A method for producing fumed alumina powder with a viscosity of 100-200 MPa / g and a tamped density of 26-64 g / L is disclosed. The alumina powder prepared contains up to 100% gamma-Al2O3, up to 5-10% theta-Al2O3, and the balance delta-Al2O3. The hydroxyl content of the prepared samples is 9.1-10.2 OH / nm, as measured by reaction with lithium aluminum hydride. 2 Again, the presence of water during the flame hydrolysis step and the subsequent post-treatment of the fumed alumina with steam or moist air does not reduce the water content of the resulting alumina.
[0012] BET surface area is 21m 2Fumed alumina powders, with a molecular weight of 0.01g / g and typically containing about 70% alpha-Al2O3, 20% delta-Al2O3 and 10% gamma-Al2O3, can be prepared according to EP 0 395 925 by a flame process using relatively high flame temperatures of 1,200-1,400 °C. In EP 0 395 925 no special measures are taken to reduce the moisture content of the resulting fumed alumina.
[0013] One possible way to reduce the moisture content of fumed aluminum oxide powders, especially the strongly absorbed water content, can be the heat treatment of the alumina under the exclusion of water. However, in addition to reducing the moisture content, such heat treatment often causes substantial structural changes, reflected for example in a significant reduction in the BET surface area of the aluminum oxide, particle agglomeration, and changes in the crystal structure phase.
[0014] Thus, according to EP 0 355 481 A1, a BET surface area of about 100 m 2 A primarily gamma fumed alumina powder with a BET surface area of 40 m2 was heat treated in a flame at temperatures exceeding 1,200°C to obtain a BET surface area of 40 m2. 2 / g, resulting in alumina containing 70-90% alpha-Al2O3.
[0015] WO 2010 / 069690 brochure describes a BET surface area of 3 to 30 m 2 WO 2010 / 069690 discloses a method for preparing a fumed aluminum oxide powder having a tamped density of at least 250 g / L, a particle size distribution of at least 85% by weight of alpha-aluminum oxide, and a particle size distribution of at least 85% by weight of alpha-aluminum oxide. The alumina powder is produced by heat treating fumed alumina granules having a predominantly gamma-Al2O3 phase and a tamped density of at least 250 g / L at 1300°C or higher, followed by grinding. WO 2010 / 069690 emphasizes that only densified alumina precursors (e.g. granules) having a tamped density of at least 250 g / L can be used as precursors in the above method.
[0016] Thus, the prior art does not teach how to obtain untreated (hydrophilic) fumed alumina powder that is both low in moisture and alpha-aluminum oxide content.
[0017] It is known from the prior art that the water content of fumed aluminum oxide can be further reduced by surface treating hydrophilic alumina with organosilanes. For example, WO 2004 / 108595 discloses a method for producing pyrogenically prepared surface-modified aluminum oxide, which comprises spraying alumina with a surface modifier in vapor form, followed by heat treatment of the resulting mixture at 50-800°C for 0.5-6 hours. This heat treatment of the surface-treated alumina completes the surface treatment reaction. [Prior art documents] [Patent documents]
[0018] [Patent Document 1] International Publication No. 2018 / 149834 Brochure [Patent Document 2] International Publication No. 2020 / 225018 Brochure [Patent Document 3] International Publication No. 2005 / 061385 Brochure [Patent Document 4] International Publication No. 2006 / 067127 Brochure [Patent Document 5] European Patent Application Publication No. 0395925 [Patent Document 6] European Patent Application Publication No. 0355481 [Patent Document 7] International Publication No. 2010 / 069690 Brochure [Patent Document 8] International Publication No. 2004 / 108595 Brochure Summary of the Invention [Problem to be solved by the invention]
[0019] Challenges and Solutions Depending on the preparation conditions, fumed alumina may contain various allotropic forms (crystalline phases), such as the thermodynamically stable alpha-Al2O3, or different transition states, such as gamma-, delta-, theta-Al2O3. Each of these different allotropic forms of alumina has its own physicochemical properties, which largely determine the fields in which it can be applied. As an example, the transition forms of Al2O3 usually have low density and high BET surface area, which makes them particularly useful, for example, as catalyst supports or additives to lithium-ion batteries. Thus, one problem addressed by the present invention is to provide a fumed alumina that is particularly suitable for use in the above applications, especially in lithium-ion batteries, consisting mainly of transition aluminum oxides, i.e., substantially free of alpha-Al2O3.
[0020] To provide fumed aluminas that are particularly suitable for water-sensitive applications such as lithium-ion batteries, it is further desirable to reduce the water content of the alumina. In particular, it is necessary to reduce the content of tightly bound water in the fumed alumina, i.e., water that cannot be removed by drying at 150° C. for 2 hours. Under normal storage conditions of the fumed alumina, e.g., in the presence of moisture in the air, the reduction in the water content in the fumed alumina will of course remain even lower.
[0021] Yet another problem addressed by the present invention is to provide good dispersibility and thixotropic properties of fumed alumina particles in various compositions, such as silicone or starved compositions. The dispersibility and thixotropic properties of fumed alumina are primarily related to the relatively small alumina particle size, narrow particle size distribution, and strong and weak particle agglomerations.
[0022] The reduction of moisture content by heat treatment is often closely associated with a change in the crystal phase, densification, a significant reduction in the BET surface area, and weak particle aggregation. Therefore, it is very difficult to obtain fumed transition alumina with a large BET surface area, low density, small alumina particles, and a narrow particle size distribution while the moisture content is significantly reduced. Therefore, it is very difficult to simultaneously achieve good dispersibility of the fumed alumina particles and low viscosity increase (thickening effect) of compositions filled with such alumina.
[0023] The overall technical problem addressed by the present invention is therefore to provide a fumed alumina powder consisting mainly of transition alumina phases, having good dispersibility in compositions and having a reduced moisture content, in particular after storage in a humid environment.A further problem addressed by the present invention is to provide a suitable method for the efficient production of such an alumina powder. After various unsuccessful attempts, the inventors have surprisingly found that the optimized process of the present invention allows for the production of such fumed alumina powders. [Means for solving the problem]
[0024] Surface Unmodified Fumed Alumina Powder The present invention relates to a) contains less than 5% alpha-Al2O3 as determined by XRD analysis; b) A numerical mean particle size d of less than 5 μm, as measured by static light scattering (SLS) after ultrasonication of a 5 wt % aqueous dispersion of alumina at 25° C. for 120 seconds. 50 having c) BET surface area of fumed alumina powder versus moisture content (KF) measured by Karl Fischer titration after drying the fumed alumina powder at 150 °C for 2 hours 150 Ratio of R 150 =KF 150 / BET is 0.0122 wt% x g / m 2 Below is the A surface-modified fumed alumina powder is provided.
[0025] The term "alumina" in the context of this specification relates to the individual compound (aluminum oxide, Al2O3), alumina-based mixed oxides, alumina-based doped oxides, or mixtures thereof. By "alumina-based" it is meant that the corresponding alumina material comprises at least 70% by weight of aluminum oxide, preferably at least 80% by weight, more preferably at least 90% by weight, more preferably at least 95% by weight, and most preferably at least 98% by weight.
[0026] The term "powder" in the present context refers to fine particles, i.e. particles having an average particle size d typically less than 50 μm, preferably less than 10 μm. 50 The present invention includes particles having the following formula:
[0027] "Fumed" aluminas, also known as "pyrolytic" or "pyrogenically produced" aluminas, are prepared by pyrolytic processes such as flame hydrolysis or flame oxidation. This involves the oxidation or hydrolysis of hydrolyzable or oxidizable starting materials, generally in a hydrogen / oxygen flame. Starting materials used for pyrolytic processes include organic and inorganic substances. Aluminum trichloride is particularly suitable. The hydrophilic aluminas thus obtained are usually in a strongly agglomerated state. "Strongly agglomerated" is understood to mean that the so-called primary particles initially produced in the fumed process are firmly bound to one another in a subsequent reaction to form a three-dimensional network. The primary particles are substantially free of pores and have free hydroxyl groups on their surface. If necessary, such hydrophilic aluminas can be hydrophobized, for example by treatment with reactive silanes.
[0028] It is known to produce pyrogenic mixed oxides by simultaneously reacting at least two different metal sources in the form of volatile metal compounds, e.g. chlorides, in a H2 / O2 flame. All components of the mixed oxide thus prepared are generally distributed homogeneously throughout the mixed oxide material, in contrast to other types of materials, such as mechanical mixtures of several metal oxides, doped metal oxides, etc. In the latter case, e.g. mixtures of several metal oxides, there may be separate regions of corresponding pure oxides, which determine the properties of such mixtures.
[0029] The fumed alumina powder of the present invention may contain crystalline phases such as alpha-, theta-, delta-, gamma-Al2O3, and amorphous alumina. The content of these phases can be measured by X-ray diffraction analysis (XRD). In such quantitative measurements, the measured X-ray diffraction pattern of a test sample is compared to the X-ray diffraction pattern of a comparison sample containing a known amount of the corresponding crystalline phase.
[0030] The fumed alumina powder of the present invention contains less than 5%, preferably less than 3%, more preferably less than 1% alpha-Al2O3, and more preferably is substantially free of alpha-Al2O3, as determined by XRD analysis. "Substantially free of alpha-Al2O3, as determined by XRD analysis," in the context of this specification, means that no peaks corresponding to alpha-Al2O3 can be identified in the X-ray crystallographic image of the sample.
[0031] The surface-untreated fumed alumina powder according to the present invention has a number-average equivalent circular diameter (ECD) of the primary particles, also called primary crystallites, d p_ECD The average equivalent circular diameter (ECD) of the primary particles is preferably 5 nm to 150 nm, more preferably 8 nm to 100 nm, and even more preferably 10 nm to 80 nm. p_ECD can be measured by transmission electron microscopy (TEM) analysis according to ISO 21363, and d p_ECD To calculate a representative value, at least 100 particles, preferably at least 300 particles, more preferably at least 500 particles should be analyzed.
[0032] As is generally known from the prior art, the average primary particle size of fumed alumina is approximately inversely proportional to its BET surface area, i.e. fumed alumina with a larger BET surface area has a proportionally smaller average primary particle size. The surface untreated fumed alumina powder according to the present invention has a number average equivalent circular diameter (ECD) d of the primary particles, as measured by transmission electron microscopy (TEM) analysis according to ISO 21363. p_ECD (in nanometers) is at least 1100 / (m 2 BET in / g アルミナ ), more preferably 1100 / (m 2 BET in / g アルミナ )~1500 / (m 2 BET in / g アルミナ ), more preferably 1120 / (m 2 BET in / g アルミナ )~1400 / (m 2 BET in / g アルミナ ), more preferably 1150 / (m 2 BET in / g アルミナ )~1300 / (m 2 BET in / g アルミナ ), more preferably 1170 / (m 2 BET in / g アルミナ )~1280 / (m 2 BET in / g アルミナ ), more preferably 1200 / (m 2 BET in / g アルミナ )~1260 / (m 2 BET in / g アルミナ ) is preferred. アルミナ m 2 / g of surface area of alumina. Thus, the heat treatment according to the present invention slightly increases the primary particle size of the resulting fumed alumina of the present invention.
[0033] The surface-modified fumed alumina powder of the present invention has reduced absorbed water content when compared to conventional fumed aluminum oxide. Some of this absorbed water is weakly bound to the Al2O3 and can be removed, for example, by drying for 2 hours at 150 °C. Another portion of the absorbed water is more strongly bound to the Al2O3 and cannot be removed by drying for 2 hours at 150 °C. This tightly bound water content is found to be virtually independent of storage conditions and to remain approximately constant under normal conditions, i.e. storage at ambient temperature and typical air humidity.
[0034] Moisture content of the surface-unmodified fumed alumina of the present invention dried at 150°C for 2 hours KF 150 can be determined by Karl Fischer titration, which can be carried out using any suitable Karl Fischer titration apparatus, for example one conforming to STN ISO 760.
[0035] The absolute moisture content of the fumed alumina powder of the present invention depends approximately linearly on its BET surface area. Surprisingly, it has been found that a specific ratio R of the reduction in moisture content of the fumed alumina to the surface area of the fumed alumina is characteristic of all fumed alumina powders according to the present invention, independent of the BET surface area.
[0036] Therefore, the BET surface area (m 2 / g) of the untreated fumed alumina powder of the present invention, after drying for 2 hours at 150°C, the water content (KF) was measured by Karl Fischer titration. 150 Ratio (unit: weight%) 150 =KF 150 / BET is 0.0122 wt% x g / m 2 or less, more preferably 0.0120 wt% x g / m 2 or less, more preferably 0.0118 wt% x g / m 2 or less, more preferably 0.0116 wt% x g / m 2 or less, more preferably 0.0114% by weight × g / m 2 or less, more preferably 0.0112 wt% x g / m 2or less, more preferably 0.0110% by weight × g / m 2 or less, more preferably 0.0108% by weight × g / m 2 or less, more preferably 0.0106% by weight × g / m 2 or less, more preferably 0.0104% by weight × g / m 2 or less, more preferably 0.0102 wt% x g / m 2 or less, more preferably 0.0100% by weight × g / m 2 or less, more preferably 0.0098% by weight × g / m 2 or less, more preferably 0.0096% by weight × g / m 2 or less, more preferably 0.0094% by weight or less × g / m 2 or less, more preferably 0.0092 wt% x g / m 2 Less than 0.0090% by weight × g / m 2 or less, more preferably 0.0088% by weight × g / m 2 or less, more preferably 0.0086% by weight × g / m 2 Less than or equal to 0.0084% by weight × g / m 2 The following is the result.
[0037] The total moisture content, KF0, of the surface-untreated fumed alumina powder of the present invention, which includes both weakly and strongly bound water, can be measured by Karl Fischer titration of alumina without pre-drying.
[0038] The BET surface area (m 2 The ratio of the total water content KF0, measured by Karl Fischer titration, to the total water content (in g / g) of the aqueous suspension, R0 = KF0 / BET, is preferably 0.0385 wt.% × g / m 2 or less, more preferably 0.0380 wt% x g / m 2 or less, more preferably 0.0375% by weight × g / m 2 or less, more preferably 0.0370% by weight × g / m 2 or less, more preferably 0.0360% by weight × g / m 2 or less, more preferably 0.0340 wt% x g / m 2or less, more preferably 0.0300% by weight × g / m 2 Less than or equal to 0.0290% by weight × g / m 2 or less, more preferably 0.0280 wt% x g / m 2 or less, more preferably 0.0270 wt% x g / m 2 Less than 0.0260% by weight × g / m 2 or less, more preferably 0.0250 wt% x g / m 2 or less, more preferably 0.0240 wt% x g / m 2 or less, more preferably 0.0230 wt% x g / m 2 or less, more preferably 0.0220 wt% x g / m 2 The following is the result.
[0039] The term "surface unmodified", in the context of this specification with respect to fumed alumina powder, means that the alumina is not surface treated, i.e., has not been modified by any surface treatment agent, and is therefore substantially hydrophilic.
[0040] The surface unmodified fumed alumina powder according to the present invention preferably has a carbon content of less than 1.0 wt%, preferably less than 0.5 wt%, more preferably less than 0.3 wt%, more preferably less than 0.2 wt%, even more preferably less than 0.1 wt%, and even more preferably less than 0.05 wt%. The carbon content can be determined by elemental analysis according to EN ISO3262-20:2000 (chapter 8).
[0041] The surface-unmodified fumed alumina powder of the present invention preferably has a methanol wettability of 15% by volume or less, more preferably 10% by volume or less, more preferably 5% by volume or less, and most preferably about 0% by volume of methanol in a methanol / water mixture. The methanol wettability of metal oxide powders such as fumed alumina of the present invention can be measured, for example, as described in detail on pages 5-6 of WO 2011 / 076518.
[0042] The surface-unmodified fumed alumina powder according to the present invention has a numerical average particle size d of less than 5 μm, more preferably 0.01 μm to 5.0 μm, more preferably 0.03 μm to 3.0 μm, more preferably 0.05 μm to 2.0 μm, more preferably 0.06 μm to 1.5 μm, more preferably 0.07 μm to 1.0 μm, more preferably 0.08 μm to 0.90 μm, more preferably 0.10 μm to 0.80 μm, as measured by static light scattering (SLS) after ultrasonicating a 5 wt % aqueous dispersion of alumina at 25° C. for 120 seconds. 50 The resulting measured particle size distribution has a mean value d, which reflects the particle size not exceeded by 50% of all particles. 50 is used to define the number average particle size.
[0043] The surface-unmodified fumed alumina powder of the present invention has a particle size d of less than 12 μm, preferably 10 μm or less, more preferably 8 μm or less, more preferably 6 μm or less, more preferably 4 μm or less, more preferably 0.20 μm to 4 μm, and more preferably 0.20 μm to 2 μm, as measured by static light scattering (SLS) after ultrasonicating a 5 wt % aqueous dispersion of alumina for 120 seconds at 25° C. 90 The resulting measured particle size distribution preferably has a particle size d that reflects a particle size not exceeded by 90% of all particles. 90 Used to define a value.
[0044] The surface-unmodified fumed alumina powder of the present invention preferably has a relatively narrow particle size distribution, which is preferably less than 20.0, more preferably less than 15.0, more preferably between 0.8 and 5.0, more preferably between 1.0 and 4.0, more preferably between 1.0 and 3.0. 90 -d 10 ) / d 50 The above surface-unmodified fumed alumina powder having a relatively small particle size and narrow particle size distribution is preferred because it has particularly good dispersibility in various compositions.
[0045] The surface-unmodified fumed alumina powder of the present invention preferably has a tamping density of 300 g / L or less, more preferably 250 g / L or less, more preferably 20 g / L to 250 g / L, more preferably 20 g / L to 200 g / L, more preferably 25 g / L to 150 g / L, more preferably 30 g / L to 130 g / L. Tamping density can be measured according to DIN ISO 787-11:1995.
[0046] The surface-unmodified fumed alumina powder of the present invention is 2 / g, preferably 20m 2 / g~220m 2 / g, more preferably 25m 2 / g~200m 2 / g, 30m 2 / g~180m 2 / g, more preferably 40m 2 / g~140m 2 / g. The specific surface area, also called simply the BET surface area, can be determined by nitrogen adsorption according to the Brunauer-Emmett-Teller method in accordance with DIN 9277:2014.
[0047] The surface-unmodified alumina powder of the present invention has a BET surface area d 2 , measured by reaction with lithium aluminum hydride, as detailed in EP 0 725 037 A1, p. 8, line 17 to p. 9, line 12. OH The number of hydroxyl groups is 7.5OH / nm 2 ~11.0OH / nm 2 , more preferably 8.0 OH / nm 2 ~10.0OH / nm 2 This method is also described in Journal of Colloid and Interface Science, Vol. 125, No. 1 (1988), pp. 61-68.
[0048] The surface-unmodified fumed alumina powder according to the present invention can be obtained after carrying out step (A) of the method of the present invention described below.
[0049] Surface Modified Fumed Alumina Powder The reduced moisture content of the surface unmodified fumed alumina of the present invention can be further significantly reduced by surface treatment of the alumina. The present invention further provides a surface-modified fumed alumina powder obtained by surface-treating the surface-untreated fumed alumina of the present invention with a surface treatment agent selected from the group consisting of organosilanes, silazanes, acyclic polysiloxanes, cyclic polysiloxanes, and mixtures thereof.
[0050] In this specification, the term "surface modification" is used interchangeably with the term "surface treatment" and refers to the chemical reaction of untreated hydrophilic alumina with a corresponding surface treatment agent that completely or partially modifies the free hydroxyl groups of the alumina.
[0051] Some particularly useful surface treatment agents suitable for obtaining the surface treated fumed alumina powder of the present invention are described below in connection with the surface treatment step (B) of the process of the present invention. The surface-modified alumina powder of the present invention can be hydrophilic or hydrophobic depending on the chemical structure of the surface treatment agent used. Preferably, a surface treatment agent that imparts hydrophobicity is used to produce a surface-treated alumina powder with hydrophobicity.
[0052] The term "hydrophobicity" in the context of this specification relates to surface treated alumina particles that have a low affinity for polar media such as water. The degree of hydrophobicity of a surface treated alumina powder can be measured by parameters such as its methanol wettability, as detailed in WO 2011 / 076518, pages 5-6. In pure water, a hydrophobic inorganic oxide (e.g., silica or alumina) completely separates from the water and floats on its surface without being wetted by the solvent. In contrast, in pure methanol, the hydrophobic oxide distributes throughout the solvent and complete wetting occurs. In measuring methanol wettability, a test oxide sample is mixed with various methanol / water mixtures and the maximum methanol content is measured where the oxide is not yet wetted, i.e., 100% of the test oxide separates from the test mixture. This methanol content (in volume %) in the methanol / water mixture is referred to as the methanol wettability. The higher the level of such methanol wettability, the more hydrophobic the inorganic oxide is.
[0053] The surface-modified fumed alumina powder of the present invention preferably has a methanol wettability in which the methanol content in a methanol / water mixture exceeds 20% by volume, more preferably 30% to 90% by volume, more preferably 30% to 80% by volume, particularly preferably 35% to 75% by volume, and most preferably 40% to 70% by volume.
[0054] The surface modified fumed alumina powder according to the invention may have a carbon content of 0.2% to 10% by weight, preferably 0.3% to 7% by weight, more preferably 0.4% to 5% by weight, more preferably 0.5% to 4% by weight, more preferably 0.5% to 3.5% by weight, more preferably 0.5% to 3.2% by weight, more preferably 0.5% to 3.0% by weight, more preferably 0.5% to 2.5% by weight, more preferably 0.5% to 2.0% by weight, more preferably 0.5% to 1.5% by weight, as determined by elemental analysis. The elemental analysis may be carried out according to EN ISO3262-20:2000 (chapter 8). The sample to be analyzed is weighed into a ceramic crucible, a combustion additive is added and the sample is heated in an induction furnace under a flow of oxygen. The carbon present is oxidized to CO2. The amount of CO2 gas is quantified by an infrared detector.
[0055] The ratio of the total water content KF0, measured by Karl Fischer titration, to the BET surface area of the surface-modified fumed alumina powder of the present invention, R0=KF0 / BET, is preferably 0.025 wt.%×g / m 2 Less than or equal to 0.022% by weight × g / m 2 Less than 0.020% by weight × g / m 2 or less, more preferably 0.015% by weight × g / m 2 or less, more preferably 0.010% by weight × g / m 2 Less than 0.005% by weight × g / m 2 The following is the result.
[0056] Many of the physicochemical properties of the surface-modified fumed alumina of the present invention correspond to those described above for its precursor, the surface-unmodified fumed alumina of the present invention. Thus, the crystal phase composition of the surface-unmodified fumed alumina of the present invention as detailed above typically does not change significantly during its surface modification, and therefore corresponds to the crystal phase composition of the surface-modified fumed alumina of the present invention.
[0057] The same is true for the particle size d measured by the SLS method. 50 , d 90, the span of the particle size distribution (d 90 -d 10 ) / d 50 However, these values are preferably measured by static light scattering (SLS) after sonication of a 5 wt % dispersion of the surface-modified alumina in methanol for 120 seconds at 25° C., instead of the water used in SLS measurements of the surface-unmodified fumed alumina. The BET surface area, tamping density, average primary particle size d of the surface unmodified fumed alumina powder of the present invention described above p_ECD The preferred range of values of corresponds to that of the surface-modified fumed alumina powder of the present invention.
[0058] Method for producing fumed alumina powder Step (A) of the method of the present invention The present invention further provides a method for producing a granular granular material having a particle size d of less than 5 μm, as measured by static light scattering, after ultrasonication of the aqueous dispersion for 120 seconds. 50 and containing less than 5% by weight alpha-Al2O3 as measured by XRD analysis, at 250°C to 1,250°C for 5 minutes to 5 hours; Substantially no water is added before, during or after step (A); A method for producing fumed alumina powder according to the invention is provided in which the temperature and duration of the heat treatment are selected such that the BET of the alumina is reduced by up to 23% relative to the BET surface area of the thermally untreated and surface untreated fumed alumina powder used.
[0059] The heat treatment of the surface untreated fumed alumina powder in the method of the present invention is carried out at a temperature of 250° C. to 1,250° C., preferably 300° C. to 1,250° C., more preferably 400° C. to 1,200° C., more preferably 500° C. to 1,200° C., more preferably 500° C. to 1,100° C., more preferably 700° C. to 1,200° C., more preferably 700° C. to 1,100° C., more preferably 1,000° C. to 1,200° C., more preferably 1,000° C. to 1,100° C. The duration of this heat treatment depends on the temperature applied and is generally 5 minutes to 5 hours, preferably 10 minutes to 4 hours, more preferably 20 minutes to 3 hours, and even more preferably 30 minutes to 2 hours.
[0060] It has been observed that the duration of the heat treatment step can have a significant effect on the properties of the resulting fumed alumina powder. Thus, if the duration of the heat treatment step, which is carried out at 250-1,250 °C, is less than 5 minutes, a significant reduction in the moisture content of the alumina is usually not observed, especially if the starting material for the heat treatment has been predried before the heat treatment and is not wet itself (e.g., if it has a moisture content of 3% by weight or less, as measured by Karl Fischer titration). Conversely, if the duration of the heat treatment step exceeds 5 hours, it usually does not bring about any significant further change in the moisture content of the resulting alumina, but the particle size of the resulting particles may increase.
[0061] The heat treatment in the method of the present invention can reduce the number of free hydroxyl groups by condensation of the free hydroxyl groups and formation of O-Al-O crosslinks. This process may involve a reduction in the BET surface area of the resulting fumed alumina. Importantly, it has been found that under the conditions used in the process of the present invention, significant reductions in water content can be achieved without substantially reducing the BET surface area of the fumed alumina.
[0062] The temperature and duration of the heat treatment in step (A) of the method of the present invention are therefore selected such that the BET of the alumina is reduced by at most 23%, preferably at most 20%, more preferably at most 17%, more preferably at most 14%, more preferably at most 11%, relative to the BET surface area of the thermally untreated and surface untreated fumed alumina powder used.
[0063] Heat treatment can also result in a crystal phase change and densification of the fumed alumina, as well as enlarging the primary particles of the resulting heat treated fumed alumina.
[0064] The heat treatment in the process of the invention can be carried out discontinuously (batchwise), semi-continuously or, preferably, continuously. In a discontinuous process, the "duration of heat treatment" is defined as the total time that the surface untreated fumed alumina is heated at a specified temperature. In a semi-continuous or continuous process, the "duration of heat treatment" corresponds to the average residence time of the surface untreated fumed alumina powder at the specified heat treatment temperature. The method of the present invention is preferably carried out continuously with the average residence time of the surface-untreated fumed alumina powder in the heat treatment step (A) being 10 minutes to 3 hours.
[0065] In the process of the present invention, the heat treatment is preferably carried out while the fumed alumina powder is moving, preferably constantly moving throughout the process, i.e., while the alumina is moving during the heat treatment. Such a "dynamic" process is in direct contrast to a "static" heat treatment process in which the alumina particles do not move (e.g., the alumina particles reside in a bed during heat treatment, such as in a muffle furnace).
[0066] It has surprisingly been found that such dynamic heat treatment methods, in combination with appropriate temperatures and durations of heat treatment, can produce small, uniform particles with relatively narrow particle size distributions that exhibit particularly good dispersibility in a variety of compositions.
[0067] The process of the present invention is preferably carried out in any suitable apparatus capable of maintaining the alumina powder at the above-specified temperature for the specified time while moving the alumina powder. Among the suitable apparatus are fluidized bed reactors and rotary kilns. Rotary kilns, in particular rotary kilns with a diameter of 1 cm to 2 m, preferably 5 cm to 1 m, more preferably 10 cm to 50 cm, are preferably used in the process of the present invention.
[0068] The fumed alumina powder is preferably moved at least temporarily during the heat treatment step (A) at a speed of movement of at least 1 cm / min, more preferably at least 10 cm / min, more preferably at least 25 cm / min, more preferably at least 50 cm / min. The alumina is preferably moved continuously at this speed of movement for the entire duration of the heat treatment step. The speed of movement in a rotary kiln corresponds to the peripheral speed of this type of reactor. The speed of movement in a fluidized bed reactor corresponds to the flow rate (fluidization velocity) of the carrier gas.
[0069] Substantially no water is added before, during or after step (A) of the method of the present invention, thus avoiding further water absorption by the fumed alumina and resulting in a heat-treated alumina powder with a lower water content. By "substantially free of water", in relation to the process of the present invention, it is meant that the amount of water added before, during or after step (A) of the process of the present invention is preferably less than 5% by weight, more preferably less than 3% by weight, more preferably less than 1% by weight, more preferably less than 0.5% by weight, based on the weight of the fumed alumina.
[0070] The heat treatment step (A) may be carried out under a flow of gas such as air or nitrogen, which gas is preferably substantially free of water or has been pre-dried. "Substantially free of water", in relation to a gas, means that the gas used in step (A) of the process of the present invention preferably has a water content of less than 5% by volume, more preferably less than 3% by volume, more preferably less than 1% by volume, more preferably less than 0.5% by volume, more preferably no steam or water vapor is added to the gas prior to use.
[0071] Step (B) of the method of the present invention The method of the present invention for producing a fumed alumina powder further comprises a step (B) of surface treating the fumed alumina powder obtained in step (A) with a surface treatment agent selected from the group consisting of organosilanes, silazanes, acyclic polysiloxanes, cyclic polysiloxanes, and mixtures thereof.
[0072] Preferred organosilanes are, for example, alkylorganosilanes of the general formulae (Ia) and (Ib). R' x (RO) y Si(C n H 2n+1 ) (Ia) R' x (RO) y Si(C n H 2n-1 ) (Ib) where R is alkyl, such as methyl, ethyl, n-propyl, i-propyl, butyl, etc. R' is alkyl or cycloalkyl, for example methyl, ethyl, n-propyl, i-propyl, butyl, cyclohexyl, octyl, hexadecyl, etc. n is 1 to 20, x+y is 3, x is 0 to 2, and y is 1 to 3.)
[0073] Among the alkylorganosilanes of formulae (Ia) and (Ib), octyltrimethoxysilane, octyltriethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane are particularly preferred.
[0074] The organosilanes used for surface treatment may contain halogens such as Cl or Br. The following types of halogenated organosilanes are particularly preferred: organosilanes of general formulae (IIa) and (IIb): X3Si(C n H 2n+1 ) (IIa) X3Si(C n H 2n-1 ) (IIb) (In the formula, X is Cl or Br, and n is 1 to 20.) organosilanes of the general formulae (IIIa) and (IIIb): X2(R')Si(C n H 2n+1 ) (IIIa) X2(R')Si(C n H 2n-1 ) (IIIb) (Wherein, X is Cl, Br, R' is alkyl, for example, methyl, ethyl, n-propyl, i-propyl, butyl, etc., or cycloalkyl, for example, cyclohexyl, etc.; n is 1 to 20.) organosilanes of general formula (IVa) and (IVb): X(R')2Si(C n H 2n+1 ) (IVa) X(R')2Si(C n H 2n-1 ) (IVb) (Wherein, X is Cl, Br, R' is alkyl, for example, methyl, ethyl, n-propyl, i-propyl, butyl, etc., or cycloalkyl, for example, cyclohexyl, etc.; n is 1 to 20.)
[0075] Among the halogenated organosilanes of the formulae (II) to (IV), dimethyldichlorosilane and chlorotrimethylsilane are particularly preferred.
[0076] The organosilanes used may contain other functional groups than alkyl or halogen substituents, for example fluorine substituents, or several other functional groups. Preferably, functionalized organosilanes of the general formula (V) are used. (R' ') x (RO) y Si(CH2) m R' (V) (wherein R' ' is an alkyl group such as methyl, ethyl, or propyl, or a halogen group such as Cl or Br; R is an alkyl group such as methyl, ethyl, or propyl; x+y is 3, x is 0-2, y is 1-3, m is 1-20, R' is methyl-, aryl (e.g., phenyl or substituted phenyl residues), heteroaryl-CF, OCF-CHF-CF, -CF 13 , -O-CF2-CHF2, -NH2, -N3, -SCN, -CH=CH2, -NH-CH2-CH2-NH2, -N-(CH2-CH2-NH2)2, -OOC(CH3)C=CH2, -OCH2-CH(O)CH2, -NH-CO-N-CO-(CH2)5, -NH COO-CH3, -NH-COO-CH2-CH3, -NH-(CH2)3Si(OR)3, -S x -(CH2)3Si(OR)3, -SH, -NR 1 R 2 R 3 (R 1 is alkyl, aryl; R 2 is H, alkyl, aryl; R 3 is H, alkyl, aryl, benzyl, C2H4NR 4 R 5 (In the formula, R 4 is H, alkyl, R 5 is H, alkyl.
[0077] Among the functionalized organosilanes of formula (V), 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, glycidyloxypropyltrimethoxysilane, glycidyloxypropyltriethoxysilane, aminopropyltriethoxysilane are particularly preferred.
[0078] Silazanes of the general formula R'R2Si-NH?SiR2R'(VI), where R is alkyl, such as methyl, ethyl, propyl, etc.; R' is alkyl, vinyl, etc., are also suitable as surface treatment agents. The most preferred silazane of formula (VI) is hexamethyldisilazane (HMDS).
[0079] Cyclic polysiloxanes such as octamethylcyclotetrasiloxane (D4), decamethylcyclopentasiloxane (D5), dodecamethylcyclohexasiloxane (D6), hexamethylcyclotrisiloxane (D6), etc. are also suitable as surface treatment agents. Among the cyclic polysiloxanes, D4 is most preferably used.
[0080] Another useful type of surface treatment agent is a polysiloxane or silicone oil of general formula (VII).
[0081] [ka]
[0082] (Wherein, Y is H, CH3, C n H 2n+1 (wherein n is 1 to 20), Si(CH3) a X b (In the formula, a is 2 to 3, b is 0 or 1, and a+b is 3.) X is H, OH, OCH3, C m H 2m+1 (wherein m is 1 to 20), R, R' are C o H 2o+1 (wherein o is 1 to 20), aryl, heteroaryl, such as phenyl and substituted phenyl residues, (CH2) k -NH2 (wherein k is 1 to 10), H; u is 2 to 1,000, preferably 3 to 100.
[0083] Among the polysiloxanes and silicone oils of formula (VII), polydimethylsiloxanes are most preferably used as surface treatment agents. Such polydimethylsiloxanes usually have a molar mass of 162 g / mol to 7,500 g / mol, a density of 0.76 g / mL to 1.07 g / mL, and a viscosity of 0.6 mPa·s to 1,000,000 mPa·s.
[0084] In step (B) of the method of the present invention, water can be used in addition to the surface treatment agent. The molar ratio of water to the surface treatment agent in step (B) of the method of the present invention is preferably 0.1-100, more preferably 0.5-50, more preferably 1.0-10, more preferably 1.2-9, more preferably 1.5-8, more preferably 2-7.
[0085] However, if it is required to obtain a surface-treated alumina powder with a low water content, the amount of water used in the process should be minimized, and ideally no water should be added during the process. It is therefore preferred that substantially no water is added before, during or after the performance of step (B). The term "substantially free of water", in the context of this specification, relates to the addition of water in an amount of less than 1% by weight of the fumed alumina powder used in step (B), preferably less than 0.5%, more preferably less than 0.1%, more preferably less than 0.01%, and most preferably no water is added. The surface treatment agent and optionally water can be used in the process of the present invention in both vapor and liquid form.
[0086] Step (B) of the method according to the invention can be carried out at a temperature between 10°C and 250°C for 1 min to 24 h. The time and duration of step (B) can be selected according to the specific requirements regarding the method and / or the targeted alumina properties. Thus, the lower the treatment temperature, the longer the hydrophobization time is usually required. In a preferred embodiment of the invention, the hydrophobization of the fumed alumina powder is carried out at 10°C to 80°C for 3 h to 24 h, preferably 5 h to 24 h. In another preferred embodiment of the invention, step (B) of the method is carried out at 90°C to 200°C, preferably 100°C to 180°C, most preferably 120°C to 160°C for 0.5 h to 10 h, preferably 1 h to 8 h. Step (B) of the method according to the invention can be carried out under a pressure of 0.1 bar to 10 bar, preferably 0.5 bar to 8 bar, more preferably 1 bar to 7 bar, most preferably 1.1 bar to 5 bar. Step (B) is most preferably carried out in a closed system at the reaction temperature and under the natural vapor pressure of the surface treatment agent used.
[0087] In step (B) of the method of the present invention, the fumed alumina powder that has been heat treated in step (A) is sprayed with a liquid surface treatment agent at ambient temperature (about 25°C), and the mixture is subsequently heat treated at a temperature between 50°C and 400°C for a period of 1 hour to 6 hours.
[0088] An alternative method of surface treatment in step (B) can be performed by treating the heat treated fumed alumina powder in step (A) with a surface treatment agent, which is in the form of vapor, and then heat treating the mixture at a temperature between 50°C and 800°C for a period of 0.5 to 6 hours.
[0089] The heat treatment after the surface treatment in step (B) can be carried out under a protective gas, for example nitrogen. The surface treatment can be carried out continuously or batchwise in a heatable mixer and dryer equipped with a spraying device. Suitable devices can be, for example, a ploughshare mixer or plate, a cyclone, or a fluidized bed dryer.
[0090] The amount of the surface treatment agent used varies depending on the type of particles and the type of surface treatment agent applied, but is usually 1 to 25% by weight, preferably 2 to 20% by weight, more preferably 5 to 18% by weight, of the surface treatment agent used relative to the amount of the fumed alumina powder heat-treated in step (A).
[0091] The required amount of surface treatment agent varies depending on the BET surface area of the fumed alumina powder used. Therefore, the BET specific surface area of the fumed alumina powder heat-treated in step (A) is 2 It is preferable to use 0.1 μmol to 100 μmol, more preferably 1 μmol to 50 μmol, and more preferably 3.0 μmol to 20 μmol of the surface treatment agent per unit area.
[0092] In optional step (C) of the process of the present invention, the fumed alumina powder subjected to heat treatment in process step (A) and / or the fumed alumina powder obtained in process step (B) is crushed, ground or milled to reduce the average particle size of the resulting alumina particles. The crushing in optional step (C) of the process of the invention can be achieved by means of all machines suitable for this purpose (eg a suitable mill). However, in most cases, it is not necessary or even desirable to carry out optional step (C) of the process of the present invention. Crushing or grinding coarse alumina particles typically results in alumina particles with a smaller average particle size, but such particles have a relatively broad particle size distribution. Such particles typically contain a relatively large proportion of fines, which complicates the handling of these crushed / ground particles. Therefore, the method of the present invention preferably does not include any crushing, grinding and / or milling steps.
[0093] Compositions containing fumed alumina powder Another object of the present invention is a composition comprising the surface-unmodified fumed alumina powder of the present invention and / or the surface-modified fumed alumina powder of the present invention. The composition according to the invention may comprise at least one binder, which binds the individual parts of the composition to one another and possibly to one or more fillers and / or other additives, thus improving the mechanical properties of the composition. Such binders may comprise organic or inorganic substances. The binders optionally comprise reactive organic substances. Organic binders may, for example, be selected from the group consisting of (meth)acrylates, alkyd resins, epoxy resins, gum arabic, casein, vegetable oils, polyurethanes, silicone resins, waxes, cellulose adhesives, and mixtures thereof. Such organic substances may cause hardening of the composition used, for example by evaporation of the solvent, polymerization, crosslinking reactions, or another type of physical or chemical change. Such hardening may take place, for example, thermally or under the action of UV radiation or other radiation. Both single (one) component systems (1-C) and multi-component systems, in particular two-component systems (2-C), may be applied as binders. In addition to or instead of a binder, the composition of the present invention may also contain a matrix polymer, such as a polyolefin resin (e.g., polyethylene or polypropylene), a polyester resin (e.g., polyethylene terephthalate), a polyacrylonitrile resin, a cellulose resin, or a mixture thereof. The fumed alumina powder of the present invention may be incorporated into such a matrix polymer or may form a coating on its surface.
[0094] Apart from the fumed alumina powder and the binder, the composition according to the invention may further contain at least one solvent and / or filler and / or other additives. The solvent used in the composition of the present invention can be selected from the group consisting of water, alcohols, aliphatic and aromatic hydrocarbons, ethers, esters, aldehydes, ketones and mixtures thereof. For example, the solvent used can be methanol, ethanol, propanol, butanol, pentane, hexane, benzene, toluene, xylene, diethyl ether, methyl tert-butyl ether, ethyl acetate and acetone. Particularly preferably, the solvent used in the composition has a boiling point of less than 300°C, particularly preferably less than 200°C. Such relatively volatile solvents can be easily evaporated or vaporized during the curing of the composition according to the present invention.
[0095] Uses of Fumed Alumina Powder The surface modification of the present invention and / or the surface modified alumina powder of the present invention can be used as a component of paints or coatings, silicones, pharmaceuticals or cosmetics, adhesives or sealants, toner compositions, lithium ion batteries, particularly the separators, electrodes and / or electrolytes thereof, to alter the rheological properties of liquid systems, as an anti-settling agent, to improve the flowability of powders, to improve the mechanical and / or optical properties of silicone compositions, as a catalyst support, in chemical mechanical planarization (CMP), and for thermal insulation. [Brief description of the drawings]
[0096] [Figure 1A] FIG. 1A shows a transmission electron microscope (TEM) image of starting material 2. [Figure 1B] FIG. 1B shows a transmission electron microscope (TEM) image of starting material 2. [Figure 2A] FIG. 2A shows a transmission electron microscope (TEM) image of starting material 2 (Example 9) heat treated at 1,200° C. [Figure 2B] FIG. 2B shows a transmission electron microscope (TEM) image of starting material 2 (Example 9) heat treated at 1,200° C. [Diagram 3] FIG. 3 shows the XRD image of starting material 2 (Example 9) heat treated at 1,200° C. [Figure 4]FIG. 4 shows an XRD image of starting material 2 (Comparative Example 3) heat treated at 1,300° C. EXAMPLES
[0097] Analysis method BET specific surface area [m 2 / g] was determined by nitrogen adsorption according to the Brunauer-Emmett-Teller method in accordance with DIN 9277:2014. Number of hydroxyl groups d for BET surface area OH [OH / nm 2 was measured by reacting a pre-dried sample of alumina powder with a lithium aluminum hydride solution as detailed in EP 0 725 037 A1, p. 8, line 17 to p. 9, line 12. This method is also described in the Journal of Colloid and Interface Science, Vol. 125, No. 1 (1988), pp. 61-68. The tamped density [g / L] was determined according to DIN ISO 787-11:1995 "General test methods for pigments and extenders - Part 11: Determination of the tamped volume and apparent density after tamping". Particle size distribution, i.e., d 10 Value, d 50 Value, d 90 value, and span(d 90 -d 10 ) / d 50 The particle size [μm] was measured by static light scattering (SLS) using a laser diffraction particle size analyzer (HORIBA LA-950) after subjecting a 5 wt % aqueous dispersion of the surface-treated alumina to ultrasonic treatment for 120 seconds at 25°C. The water content [wt %] was measured by Karl Fischer titration using a Karl Fischer titrator. Average equivalent circular diameter (ECD) of primary particles p_ECD was measured by transmission electron microscopy (TEM) as per ISO 21363. X-ray diffraction analysis (XRD) was performed with a transmission diffractometer from Stoe&Cie (Dortmund, Germany) using CuK alpha radiation (excitation: 30 mA, 45 kV, OED). For quantitative determination of alpha-Al2O3, the measured X-ray diffraction patterns of the test samples were compared with those of comparison samples containing 100% and 80% alpha-Al2O3.
[0098] Starting materials BET surface area is 121m 2 Fumed alumina, 0.01 wt. / g, was prepared as described on page 35 of WO 2004 / 108595 (Aluminum Oxide I) and used as starting material 1. BET surface area is 50m 2 Fumed alumina having a mean particle size of 1.0 μm / g was prepared according to Example 3 of WO 2006 / 067127 and used as starting material 2. The mean primary particle size of the particles, d p_ECD The average equivalent circular diameter (ECD) of the primary particles was found to be 21.2 nm (=1062 / BET).
[0099] Example 1 The starting material 1 was subjected to a heat treatment at 400°C in a rotary kiln with a diameter of about 160 mm and a length of about 2 m. The average residence time of the alumina in the rotary kiln was 1 hour. The rotation speed was set at 5 rpm, and the throughput of the alumina was about 1 kg / hour. Dry, sterilized compressed air was pumped through the kiln for about 1 m. 3 The air was continuously fed to the kiln outlet (countercurrent to the heat-treated alumina flow) at a flow rate of 10000g / hr, and temperature-controlled air was fed to the convection in the tubes. This process was carried out smoothly. No clogging of the rotary kiln was observed. The physicochemical properties of the obtained heat-treated alumina are shown in Table 1.
[0100] Examples 2-4 and Comparative Examples 1-2 were carried out in the same manner as Example 1, except that a heat treatment temperature of 700-1,300 °C was applied. No clogging of the rotary kiln was observed in Examples 2-4 at 700-1,100 °C, but some clogging was observed in Comparative Example 1 (heat treatment at 1,200 °C). In Comparative Example 2 (heat treatment at 1,300 °C), so much clogging was observed that the experiment had to be stopped. Therefore, the obtained products were not further analyzed. The physicochemical properties of the obtained heat-treated aluminas (except Comparative Example 2) are shown in Table 1.
[0101] Table 1 shows the starting material 1 (BET: 121m 2 The physicochemical properties of the fumed alumina powder obtained by heat treatment (T1000:1 / g, tamping density: 52 g / L) are shown.
[0102] The BET surface area, tamped density and particle size of starting material 1, as well as the composition of the crystalline phase, do not change significantly in Examples 1-4, where the heat treatment is carried out at a temperature below 1,100° C. In Examples 1-4, the total water content of starting material 1 decreased from 4.76 wt.% to 1.93-2.72 wt.%, and the content of strongly bound water decreased from 1.54 wt.% to about 1 wt.%.
[0103] Conversely, at 1,200°C (Comparative Example 1), there was a sharp decrease in the BET surface area (25.6%) and a decrease in the tamping density (26.9% increase) and particle size, e.g., d 50 A significant increase in both the grain size and grain size (a dramatic increase from 0.11 μm to 3.63 μm) was observed (Table 1). In the XRD images of the samples from Examples 1-4 and Comparative Example 1, no alpha phase of Al2O3 was observed. Comparative Example 2, carried out at 1,300° C., had to be discontinued because the rotary kiln used became clogged and further experiments could not be carried out.
[0104] Example 5 The starting material 2 was subjected to a heat treatment at 400°C in a rotary kiln with a diameter of about 160 mm and a length of about 2 m. The average residence time of the alumina in the rotary kiln was 1 hour. The rotation speed was set at 5 rpm, and the throughput of the alumina was about 1 kg / hour. Dry, sterilized compressed air was pumped through the kiln for about 1 m. 3 The air was continuously fed to the kiln outlet (countercurrent to the heat-treated alumina flow) at a flow rate of 10000 / hr, and temperature-controlled air was fed to the convection in the tubes. This process was carried out smoothly. No clogging of the rotary kiln was observed. The physicochemical properties of the obtained heat-treated alumina are shown in Table 2.
[0105] Examples 6 to 9 and Comparative Example 3 were carried out in the same manner as in Example 5, except that the heat treatment temperature was 700 to 1,300°C. No clogging of the rotary kiln was observed in Examples 6 to 9, but severe clogging was observed in Comparative Example 3. The physicochemical properties of the obtained heat-treated alumina are shown in Table 2. The average primary particle size d p_ECD The average equivalent circular diameter (ECD) of the primary particles was 27.6 nm (=1243 / BET). Table 2 shows the physicochemical properties of the fumed alumina powder obtained by heat treatment of starting material 2 (BET: 50m 2 / g, tamped density = 95g / L).
[0106] The BET surface area, tamped density and particle size of starting material 2, as well as the composition of the crystalline phase, did not change significantly in Examples 5-9 (Figure 3 for Example 9) where the heat treatment was performed at temperatures below 1,200 °C. In Examples 5-9, the total water content of starting material 2 decreased from 2.09 wt% to 0.98-1.25 wt%, and the content of strongly bound water decreased from 0.62 wt% to about 0.45-0.55 wt%.
[0107] Conversely, at 1,300°C (Comparative Example 3), there was a sharp decrease in BET surface area (24%) and a decrease in tamping density (42% increase) and particle size, e.g., d 50There was a dramatic increase in both the grain size and grain size (a dramatic increase from 0.11 μm to 2.48 μm). At the same time, there was a significant change in the crystalline phase composition, especially the appearance of large amounts of alpha-Al2O3 (Table 2, Figure 4).
[0108] 1A and 1B show transmission electron microscope (TEM) images of starting material 2. FIG. 2A and 2B show transmission electron microscope (TEM) images of starting material 2 (Example 9) heat-treated at 1,200° C. As can be seen from the TEM analysis, the average equivalent circular diameter d of the primary particles of alumina is p_ECD increases from 21.2 nm (starting material 2) to 27.6 nm (example 9).
[0109] [Table 1]
[0110] [Table 2]
Claims
1. a) less than 5 wt.% alpha-Al as determined by XRD analysis 2 O 3 Including, b) A numerical average particle size d of less than 5 μm, as measured by static light scattering (SLS) after ultrasonic treatment of a 5 wt. % aqueous dispersion of alumina at 25° C. for 120 seconds. 50 having c) The water content, KF, measured by Karl Fischer titration after drying the fumed alumina powder at 150° C. for 2 hours, relative to the BET surface area of the fumed alumina powder. 150 Ratio of R 150 =KF 150 / BET is 0.0122 wt% x g / m 2 Below is the Surface unmodified fumed alumina powder.
2. Alpha Al as determined by XRD analysis 2 O 3 The fumed alumina of claim 1 , which is substantially free of
3. The BET surface area of the alumina is 20 m 2 / g~220m 2 2. The fumed alumina of claim 1, wherein the alumina content is 1 / g.
4. 2. The fumed alumina of claim 1, wherein the alumina has a tamped density of less than or equal to 250 g / L.
5. The number average equivalent circular diameter d of the primary particles of the alumina is measured by transmission electron microscopy (TEM) in accordance with ISO 21363. p-ECD (in nanometers) is at least 1100 / (m 2 / g unit of the surface area of the alumina BET alumina 2. The fumed alumina of claim 1, wherein
6. The alumina has a water content, KF, measured by Karl Fischer titration, relative to the BET surface area. 0 The ratio of KF 0 / BET is 0.0385 wt% x g / m 2 2. The fumed alumina powder of claim 1, wherein:
7. 2. A surface-modified fumed alumina powder obtained by surface-treating the fumed alumina according to claim 1 with a surface treatment agent selected from the group consisting of organosilanes, silazanes, acyclic polysiloxanes, cyclic polysiloxanes and mixtures thereof.
8. The aqueous dispersion was ultrasonicated for 120 seconds, and then the particle size d of less than 5 μm was measured by static light scattering. 50 and less than 5 wt. % alpha-Al as determined by XRD analysis. 2 O 3 The method includes a step (A) of subjecting a surface-untreated fumed alumina powder containing the above-mentioned compound to a heat treatment at 250° C. to 1,250° C. for 5 minutes to 5 hours, Substantially no water is added before, during or after the step (A); The temperature and duration of the heat treatment are selected so that the BET surface area of the alumina is reduced by up to 23% relative to the BET surface area of the thermally untreated and surface untreated fumed alumina powder used; A method for producing the fumed alumina powder according to claim 1.
9. The method of claim 8 , wherein the heat treatment occurs while the fumed alumina powder is in motion.
10. 10. The method of claim 8 or claim 9, wherein the fumed alumina powder is moving at a motion speed of at least 1 cm / min during the heat treating step (A).
11. The method of claim 8, wherein the heat treatment is carried out in a rotary kiln.
12. 9. The method of claim 8 for producing the surface modified fumed alumina powder of claim 7, further comprising a step (B) of surface treating the fumed alumina powder obtained in step (A) with a surface treatment agent selected from the group consisting of organosilanes, silazanes, acyclic polysiloxanes, cyclic polysiloxanes and mixtures thereof.
13. 13. The method of claim 12, wherein substantially no water is added before, during or after step (B).
14. A composition comprising the fumed alumina powder of claim 1.
15. 2. Use of the fumed alumina powder of claim 1 in paints or coatings, silicones, pharmaceuticals or cosmetics, adhesives or sealants, toner compositions, as a component of lithium ion batteries, for modifying the rheological properties of liquid systems, as an anti-settling agent, for improving the flowability of powders, for improving the mechanical and / or optical properties of silicone compositions, as a catalyst support, in chemical mechanical planarization (CMP), and for thermal insulation.